Promoting authenticity and engagement through inquiry, dialogue, and personal connections: an action research project based on Weinstein’s “Train of Thought” - Fabiano, Theodore F. (Kansas State University, 2022)
This action research project investigates the effects of a critical literacy practice, the “Train of Thought,” as applied by students to a complex text. It is implemented at a time when cries of “students aren’t reading” and declining test scores are tempered with calls for relevance and equity. The intention is to determine to what extent this inquiry-based strategy creates opportunities for advanced literate behaviors while inviting student ownership of the learning experience. The theoretical framework is based on constructivist learning theory and critical learning theory. The study takes place during the first semester of the 2021 school year and January of 2022 at Mountain Peak High School, a northern Colorado 9-12 public school with an approximate enrollment of 715 students. Junior-level students from eight classes -- five on-level ELA 11 classes and three Advanced Placement English Language classes -- generate the artifacts and reflections used for this study. Two colleagues join me in implementing the strategy and reflecting on the experience. Students are prompted to use a set of criteria to generate an “interior monologue” of their thinking about a text, followed by small group and whole class discussion. Four possible outcomes of their thinking-- speculating, clarifying the question, eliminating possible answers, and demonstrating confusion – are coded for one student product from each class to identify the benefits of “thinking on paper.” In this study, teachers and students are interviewed, and participating students are surveyed to determine attitudes toward the strategy and gain multiple perspectives on its effectiveness. The goal of the “Train of Thought” is to address concerns that students are ill-prepared for 21st century demands of independent thinking and problem-solving by providing guided training and putting power (and expectations of initiative) in the hands of the student.
Keywords: Inquiry; Action research; Engagement; Student agency; Collaboration; Authenticity; Inquiry-based learning; Student-centered learning; Scaffolded reading experience; Student ownership; Critical reading; Metacognition